Macrozoobenthos in the intertidal zone of the Ly Son island - Hong, Phan Thi Kim; Khang, Nguyen An; Hoc, Dao Tan; Ngan, Nguyen Thi My; Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2019)
The surveys of macrozoobenthos fauna of Ly Son tidal area were carried out at 8 stations in September 2016. The 4 replicate samples were collected in high, middle and low tidal zones at each station. The results record 92 taxa of mollusc (accounting for 35% of total number of taxa), 76 taxa of crustacean (29%), 71 taxa of polychaete (27%) and 22 taxa of echinoderm (9%). Among them, there are 7 species of valuable resources that were exploited for food such as sea cucumber (Holothuria (Semperothuria) cinerascens), collector urchin (Tripneustes gratilla), diadema urchin (Echinothrix diadema), Diadema savignyi (belonging to Echinoderma), strawberry conch (Strombus luhuanus), goldmouth turban (Turbo chrysostomus) and bearded horse mussel (Modiolus barbatus). Some species with beautiful shapes and colors are used for handycraft such as black-lip pearl oyster (Pinctada margaritifera), small giant clam (Tridacna maxima), Chinese cowrie (Cypraea chinensis)... The densities of mactozoobenthos vary from 38 to 1,632 individuals/m2 between stations and tend to increase from high to low tide zones; from sandy bottom and shore rock to dead coral habitats covered by seaweed and seagrass bed.